Refusal Expression in L2 and its Comparison with Native Speaker: A Study Case in the Japanese Language - Lisda Nurjaleka (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This study aims to fill the gap of the comparison study between Japanese learners and native Japanese speakers, focused on the semantic formula of refusal act. Sixteen Japanese native speakers and twenty-two Indonesian learners are the subjects of this study. We use a questionnaire or Discourse Completion Test (DCT) to collect the data, and we use the semantic formula by Ito and Ikeda to analyze the refusal utterances. This paper reveals that Indonesian Japanese learners tended to not aware of different social status levels and use different semantic formulas in Japanese. The lack of knowledge of the pragmatic competence within the use of speech act is the main problem in Japanese education.